Cropping system research in semi-arid regions of Central America; (a proposal) (Centro Agronómico Tropical de Investigación Y Enseñanza (CATIE), Turrialba (Costa Rica). Programa de Cultivos Anuales, 2014)
Dat. num. 2 mapas.